The Effect of Inside-Outside Circle Learning Strategy Uses Visual Media to The Students’ Speaking Ability - Syafaat, Syafaat; Hidayani, Selnistia; Octaviana, Fadila (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The ability to speak is transparent and processes sound, understands others, expresses thoughts, and interacts with others based on student development. Based on the researchers’ observations, Al-Rahmah High School the students still need to improve their speaking skills; the researchers applied Inside Outside Circle (IOC) to learn strategies on students’ speaking abilities. This research examines the effectiveness of the Inside Outside Circle (IOC) learning strategy on language competency using image media. This research is exper’mental, with only one post-test in one experimental class and one control class. The samp’e in this study was eleventh-grade students in two science major classes at Al-Rahmah. Research analysis of the first class as an experimental class in class eleven majoring in science one and the second class as a control class in class eleven majoring in science two. This research used t-test analysis techniques. The study conducted on Ar-Rahmah High School students shows that IOC learning affects students’ speaking abilities, indicated by t-count = 6.28 > t-table 2.00. we can conclude that there is significant effect of IOC learning strategy use visual media and it cand conclude that students speaking ability increased by using IOC learning strategy.